Digital Transformation and Agile Leadership: Bibliometrics Analysis and Future Avenue - I Komang Mahayana Putra; I Ketut Pasek; I Wayan Edi Arsawan (Journal of International Conference Proceedings, 2022)
Turbulence and globalization require organizations to improve their capability to win the competition, face turbulence, improve performance and competitiveness. The literature reveals that digital transformation and leadership play an important role in building agility and resilience but there is no map of the relationship between these two constructs. The present study aims to identify research trends in the Scopus database through the identification of keywords digital transformation and agile leadership in the last two decades. The results show that the visual trend is increasing in the number of publications, impact factors, citations trend and author-country networks. This systematic literature review provides guidance on how organizations are implementing digitization for building organizational agility and resilience